Report of the Working Group on Non-Communicable Diseases for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission Government of India, 2001)
The Working Group on Non-Communicable Diseases (NCDs) for India’s Tenth Five-Year Plan (2002–2007) provides a comprehensive analysis of the rising burden of NCDs, including cancer, cardiovascular diseases, diabetes, and mental health disorders. The report highlights the epidemiological trends, emphasizing the urgent need for prevention, early detection, and effective management strategies. Proposed initiatives include the expansion of regional cancer centers, trauma care units, mental health facilities, and geriatric care programs, alongside oral health promotion. The group advocates for public awareness campaigns, school-based health education, and the integration of modern healthcare technologies such as telemedicine. Financial commitments totaling Rs. 1648 crores are recommended, with targeted allocations for cancer control, cardiovascular programs, blindness prevention, and mental health initiatives. Additionally, the report underscores the importance of research and development through ICMR and the need to address healthcare costs at national, state, and local levels. Overall, the document provides a strategic framework for combating NCDs in India, emphasizing multi-sectoral collaboration, infrastructure development, and comprehensive public health interventions to mitigate future disease burden.
Government of India Planning Commission May-2001
Keywords: NCD Prevention; Cancer Control; Cardiovascular Diseases; Diabetes Management; Mental Health; Public Health Policy; Health Infrastructure; Geriatric Care; Oral Health; Health Education; Research and Development